E-GOVERNMENT PRACTICES AND ORGANISATIONAL PERFORMANCE IN MALAYSIA LOCAL GOVERNMENTS (Journal of Technology and Operations Management, 2024)
E-Government is implemented to enhance the quality and performance of services in the public sector. Malaysia faces various issues and challenges in developing e-Government, including weaknesses in organisational performance. To manage the services, continuous effort and cooperation from all parties involved in administration are necessary. This study explores the literature on e-Government and organisational performance to see the breadth of e-Government's contribution to the performance of the local government sector. An empirical study using quantitative research methods was conducted on local government in Malaysia. A total of 149 questionnaires were distributed to local authorities in Malaysia, from which 87 questionnaires were completed and returned. The study findings indicate that the implementation of e-Government does not have a significant impact on organisational performance. The difference results may be attributed to variations in the e-Government development index between developed and developing countries. Additional factors, such as the difference acceptance level and challenges in implementation may further affect the outcomes. It is possible that other intermediate factors or variables exist within the relationship, which could allow for the study to be tested indirectly.